Research priorities for pregnancy hypertension: a UK priority setting partnership with the James Lind Alliance. Issue 7 (14th July 2020) - Ho, Alison; Webster, Louise; Bowen, Liza; Creighton, Fiona; Findlay, Sarah; Gale, Chris; Green, Marcus; Gronlund, Toto; Magee, Laura A; McManus, Richard J; Mistry, Hiten D; Singleton, Gemma; et al.
Abstract : Objectives: To identify research priorities for hypertensive disorders of pregnancy from individuals with lived experience and healthcare professionals. Design: Prospective surveys and consensus meetings using principles outlined by the James Lind Alliance. Setting: UK. Methods: A steering group was established and 'uncertainties' were gathered using an online survey and literature search. An interim online survey ranked long-listed questions and the top 10 research questions were reached by consensus at a final prioritisation workshop. Participants: Women, partners, relatives and friends of those with lived experience of pregnancy hypertension, researchers and healthcare professionals. Results: The initial online survey was answered by 278 participants (180 women with lived experience, 9 partners/relatives/friends, 71 healthcare professionals and 18 researchers). Together with a literature search, this identified 764 questions which were refined into 50 summary questions. All summary questions were presented in an interim prioritisation survey that was answered by 155 participants (87 women with lived experience, 4 partners/relatives/friends, 49 healthcare professionals and 15 researchers). The top 25 highest ranked questions were considered by the final prioritisation workshop. The top 10 uncertainties were identified by consensus and ranked as follows in order of priority: long-term consequences of pregnancy hypertension (for the woman and baby), short-term complications of pregnancy hypertension (for the woman and baby), screening tests for pre-eclampsia, prevention of long-term problems (for the woman and baby), causes of pregnancy hypertension, prevention of recurrent pregnancy hypertension, educational needs of healthcare professionals, diagnosis of pre-eclampsia, management of pregnancy hypertension, provision of support for women and families. Conclusions: Research priorities shared by those with lived experience of pregnancy hypertension and healthcare professionals have been identified. Researchers should use these to inform the choice of future studies in this area.